What can we learn from programme reports? Lessons from international forestry programmes. Issue 2 (17th February 2017) - Ulybina, Olga
ABSTRACT: This article discusses the current state of knowledge sharing and reporting by international development agencies and NGOs by examining several major internationally supported forestry programmes in Kyrgyzstan. The programme reporting practices of a selection of international development agencies and their limitations are discussed in light of recent developments in the areas of open data, knowledge management, and global reporting standards. The article proposes that focusing on learning and knowledge sharing rather than merely accountability, as well as building on corporate reporting standards, could help establish an easy-to-use global knowledge pool to eventually ensure more effective, evidence-based international development.